Local Transmission Plays No Important Role in the Occurrence of Multidrug-Resistant Tuberculosis in Immigrants to Canada: An In-depth Epidemiologic Analysis. (27th January 2021) - Long, Richard; Lau, Angela; Egedahl, Mary Lou; Paulsen, Catherine; Heffernan, Courtney; Edwards, Brett; Cooper, Ryan
Abstract: Background: Multidrug-resistant (MDR) tuberculosis has increased among migrants in Canada. The cause(s) of this increase is unknown. Methods: We performed a retrospective cohort study in a Canadian province with substantially increased immigration between 1982–2001 and 2002–2019. The proportion of MDR tuberculosis among migrants arriving from high MDR (HMDR) tuberculosis burden countries during these 2 periods was used to estimate the proportion of cases due to immigration versus change in proportion in the country of birth. Epidemiologic, spatiotemporal, and drug resistance pattern data were used to confirm local transmission. Results: Fifty-two of 3514 (1.48%) foreign-born culture-positive tuberculosis patients had MDR tuberculosis: 8 (0.6%) in 1982–2001 and 44 (2.0%) in 2002–2019. Between time periods, the proportion of MDR tuberculosis among migrants with tuberculosis from HMDR tuberculosis countries increased from 1.11% to 3.62%, P = .003; 31.6% attributable to recent immigration and 68.4% to a higher proportion of MDR tuberculosis in cases arrived from HMDR tuberculosis countries. No cases of MDR tuberculosis were attributable to local transmission. Conclusions: In stark contrast to HMDR tuberculosis countries, local transmission plays no important role in the occurrence of MDR tuberculosis in Canada. Improved tuberculosis programming in HMDR tuberculosis countries is urgently needed. Abstract : Recent increase in MDR tuberculosis in Canada is not due to immigration but rather an increase in the proportion of MDR tuberculosis in cases arrived from high MDR tuberculosis burden countries. Local transmission of MDR tuberculosis is not a contributor.